Analysis of MSME Actors' Perception in West Java Toward the Use of Artificial Intelligence (AI) as an Effort to Improve Operational Efficiency - Rahma, Rana Ardila; Fasa, Nadia; Gultom, Louisa Paulina Febriana; Azhar, Haniyyah; Putri, Melodi Laora (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
This study aims to analyze the perceptions of Micro, Small and Medium Enterprises (MSMEs) in West Java regarding the use of Artificial Intelligence (AI) as an effort to increase operational efficiency. The method used is quantitative research with a survey via questionnaire distributed to 100 MSME players. Data analysis includes descriptive statistics to identify the level of understanding, benefits, barriers, and expectations regarding AI adoption. The research results show that 32% of respondents have used AI, with the majority using it for sales data analysis. As many as 75% of AI users find it easy to operate the technology, and 84% state that the cost of use is relatively affordable. The main obstacle is a lack of understanding of the technology, which has led to low widespread adoption of AI. As many as 52% of respondents expressed interest in taking AI training. This research concludes that although AI provides significant benefits in increasing efficiency, technological literacy and more affordable access are needed to accelerate digital transformation in the MSME sector. Recommendations include developing AI-based training and providing technology solutions that are easier to implement.